Genetic and Environmental Stability of Intelligence in Childhood and Adolescence. (June 2014) - Franić, Sanja; Dolan, Conor V.; van Beijsterveldt, Catherina E.M.; Pol, Hilleke E. Hulshoff; Bartels, Meike; Boomsma, Dorret I.
<x content-type="archive" xml:space="preserve">Abstract</x> The present study examined the genetic and environmental contributions to the temporal stability of verbal, non-verbal and general intelligence across a developmental period spanning childhood and adolescence (5–18 years). Longitudinal twin data collected in four different studies on a total of 1, 748 twins, comprising 4, 641 measurement points in total, were analyzed using genetic adaptations of the simplex model. The heterogeneity in the type of instrument used to assess psychometric intelligence across the different subsamples and ages allowed us to address the auxiliary question of how to optimally utilize the existing longitudinal data in the context of gene-finding studies. The results were consistent across domains (verbal, non-verbal and general intelligence), and indicated that phenotypic stability was driven primarily by the high stability of additive genetic factors, that the stability of common environment was moderate, and that the unique environment contributed primarily to change. The cross-subscale stability was consistently low, indicating a small overlap between different domains of intelligence over time. The high stability of additive genetic factors justifies the use of a linear combination of scores across the different ages in the context of gene-finding studies.